2016
DOI: 10.1001/jamaoto.2016.1927
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy for Cutaneous Squamous Cell Carcinoma on the Head and Neck

Abstract: Rigorous study of SLNB for cutaneous SCC incorporating prospectively-collected comprehensive data sets based on standardized treatment algorithms is justified with potential to modify clinical practice. Our study demonstrates the critical importance of serial sectioning and IHC of the SLNB specimen for accurate diagnosis. Use of the NCCN guidelines may facilitate identification of patients with SCC at high risk for nodal metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 36 publications
5
49
1
1
Order By: Relevance
“…A literature review of SLN in SCC found that the majority of false negative biopsies came before the year 2000, in which, a combination of radioisotope and blue dye was not used in SLN identification . Therefore, a combined technique of preoperative lymphoscintigraphy with a tracer and blue dye has been considered to be a reliable and promising technique in SCC . Therefore, the proposed method of SLNB in the setting of SCC should include pre‐operative lymphoscintigraphy performed using technetium sulfur colloid injected intradermally at the site of the primary lesion either on the same day or day before the SLNB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A literature review of SLN in SCC found that the majority of false negative biopsies came before the year 2000, in which, a combination of radioisotope and blue dye was not used in SLN identification . Therefore, a combined technique of preoperative lymphoscintigraphy with a tracer and blue dye has been considered to be a reliable and promising technique in SCC . Therefore, the proposed method of SLNB in the setting of SCC should include pre‐operative lymphoscintigraphy performed using technetium sulfur colloid injected intradermally at the site of the primary lesion either on the same day or day before the SLNB.…”
Section: Resultsmentioning
confidence: 99%
“…Intraoperative hand‐held gamma probe then provides guidance to the location of the SLN. A small incision and blunt dissection will allow the surgeon to gain access to the SLN while preserving nearby neurovascular structures …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,26,27 A cirurgia é o tratamento de eleição para o CEC, sendo que as margens de segurança estão definidas pelo Consenso Europeu EDF-EADO-EORTC, baseadas na classificação de Brantsch. 16 Tendo em conta que conhecer a espessura do tumor no pré-operatório pode não ser viável, deve-se ter em conta outros critérios também referidos pelo Consenso Europeu EDF--EADO-EORTC, como por exemplo o diâmetro do tumor, 16 de uso mais prático na clínica.…”
Section: Revista Spdv 75(1); Cancro Cutâneo De Cabeça E Pescoço; Miguunclassified